PENERAPAN TEKNIK PEMBELAJARAN SPOTLIGHT DISERTAI KARTU PANGGILAN UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 KOTO XI TARUSAN TAHUN PELAJARAN 2013/2014 - Asyura, Ira; Zuzano, Fazri; Fitri, Dewi Yuliana (STKIP PGRI Sumbar, 2013)
This research was background by the learning outcomes of studentâs mathematic in SMPN 1 Koto XI Tarusan was low.Â This was one of the factors may indicate the studentâs understanding of mathematics concepts was still low.Â The aim of this research was to determine whether studentâs understanding of mathematics concepts by applying study with Spotlight accompanied Call Card techniques better than understanding of mathematic concept in convensional study to the studentâs at the VIII grade in SMPN 1 Koto XI Tarusan. The type of the research was experimental research with random sampling techniques.Â The population in the research were the students of VIII grades in the school year 2013/2014. The selected sample was VIII.2 as the experimental class and VIII.3 as the control class.Â The instrument used in this study was the test of understanding concept in the form of essays.Â The data obtained were analyzed by using a normality test, homogeneity test and t-test. Based on mathematical final test value of the student in both of sample classes is got experimental class with Â = 62 higher than the control class with Â = 50. The results of uji-t are got t count value = 2.44 and Â Â Â Â Â Â Â Â t table = 1.645, because of t count > t table consequently hipetesis in this research was accepted.Â Thus, it can be concluded that the ability of understanding of mathematic concept by using the study with Spotlight accompanied Call Card techniques better than the studentâs understanding of mathematic concept with conventional study to the studentâs at the VIII grade in SMPN 1 Koto XI Tarusan at the level of 95 %.